CircRNA_1156 Attenuates Neodymium Nitrate-Induced Hepatocyte Ferroptosis by Inhibiting the ACSL4/PKCβII Signaling Pathway - Ning Wang; Jing Leng; Jing Xu; Kelei Qian; Zhiqing Zheng; Gonghua Tao; Ping Xiao; Xinyu Hong (Antioxidants, 2025)
Ferroptosis, a form of regulated cell death driven by lipid peroxidation, has been implicated in the pathogenesis of liver diseases. This study investigates the role of circRNA_1156 in neodymium nitrate (Nd(NO3)3)-induced hepatocyte ferroptosis. Our in vitro experiments revealed that exposure to Nd(NO3)3 (1.2 µM) significantly reduced the viability of AML12 hepatocytes (p < 0.01), increased levels of reactive oxygen species (ROS) and malondialdehyde (MDA) (p < 0.001), and depleted glutathione (GSH) (p < 0.001). However, overexpression of circRNA_1156 effectively reversed these effects and suppressed the expression of ACSL4 and PKCβII (p < 0.01). In our in vivo experiments, chronic exposure to Nd(NO3)3 (7–55 mg/kg for 180 days) induced hepatic iron deposition, mitochondrial damage, and activation of the ACSL4/PKCβII pathway (p < 0.01). These adverse effects were significantly ameliorated by circRNA_1156 overexpression (p < 0.05). Our findings identify circRNA_1156 as a novel inhibitor of Nd(NO3)3-induced ferroptosis via downregulation of the ACSL4/PKCβII pathway, providing valuable therapeutic insights for hepatotoxicity caused by rare earth element compounds.